2014
DOI: 10.1186/1532-429x-16-26
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of cocaine on the heart assessed by cardiovascular magnetic resonance at 3T

Abstract: BackgroundCocaine is an addictive, sympathomimetic drug with potentially lethal effects. The prevalence and features of cocaine cardiotoxicity are not well known. We aimed to assess these effects using a comprehensive cardiovascular magnetic resonance (CMR) protocol in a large group of asymptomatic cocaine users.MethodsConsecutive (n = 94, 81 males, 36.6 ±7 years), non-selected, cocaine abusers were recruited and had a medical history, examination, ECG, blood test and CMR. The CMR study included measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 48 publications
2
55
0
2
Order By: Relevance
“…Furthermore, neither the T2 ratio nor native myocardial T1 as indicators of diffuse myocardial edema were elevated compared with healthy controls (Table 4). While these data are in line with Maceira et al, 13 Aquaro et al found edema in 47% (n=14) of their patients. Given that 43% (n=13) of the Aquaro et al patients had positive urine assay for cocaine metabolites at the time of CMR, the authors suggested a correlation between recent cocaine use and the presence of focal edema.…”
Section: Focal and Diffuse Myocardial Injury In Casupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, neither the T2 ratio nor native myocardial T1 as indicators of diffuse myocardial edema were elevated compared with healthy controls (Table 4). While these data are in line with Maceira et al, 13 Aquaro et al found edema in 47% (n=14) of their patients. Given that 43% (n=13) of the Aquaro et al patients had positive urine assay for cocaine metabolites at the time of CMR, the authors suggested a correlation between recent cocaine use and the presence of focal edema.…”
Section: Focal and Diffuse Myocardial Injury In Casupporting
confidence: 91%
“…14 In contrast, Maceira et al observed a significant increase of LVESVi (30±8 mL/m 2 vs. 26±5 mL/m 2 ; P≤0.01) and LV mass index (76±15 g/m 2 vs. 69±4 g/m 2 ; P≤0.01) as well as a significant decrease in LVEF (59±5% vs. 68±4%; P≤0.01) compared with their healthy control group. 13 Nevertheless, all obtained LVEDVi, LVESVi, LV mass index and LVEF in CA in the present and the 2 recent studies were within the normal range according to recently established reference values for CMR. 34 Furthermore, we observed mild diastolic dysfunction only in 2 CA, which was not associated with increased LV mass or hypertension.…”
Section: Ca Cardiovascular Statussupporting
confidence: 71%
See 1 more Smart Citation
“…Using cardiovascular magnetic resonance imaging, Maceira et al [60] found that approximately 30% of nearly 100 long-term asymptomatic cocaine users had evidence of cardiovascular disease. Similarly, Sharma et al [34] performed 12-lead electrocardiograms (ECGs) in nearly 100 cocaine-dependent subjects and found long-lasting effects of cocaine use on cardiac conduction and the autonomic nervous system that are likely to increase the risk of adverse cardiovascular events even between episodes of cocaine use.…”
Section: Long-term Cardiovascular Consequencesmentioning
confidence: 99%
“…Increased QT interval is most common, but prolongation of QRS duration and PR interval may also be noted. Investigators have also noted increased left ventricular end-systolic volume, left ventricular mass index, and right ventricular end-systolic volume with decreased left and right ventricular ejection fraction with long-term use [60].…”
Section: Long-term Cardiovascular Consequencesmentioning
confidence: 99%